2021
DOI: 10.37482/0536-1036-2021-6-24-37
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Elemental Composition of Conifer Tree Rings

Abstract: Distribution of chemical elements in tree rings bears important information on various biogeochemical processes. In order to achieve a reliable interpretation of the information, it is necessary to know the degree of variation in the content of chemical elements both at the level of the entire species and at the level of individual trees. The research aims to determine which chemical elements have a stable distribution in the trunks of a number of conifers: Siberian spruce (Picea obovata Ledeb.), Scots pine (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Tree-ring widths are detrended because of the non-linear growth curve. The counts of some elements also have long-term trends [ 12 , 13 ]. The best example is Ca, which decreases from the pith to the bark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tree-ring widths are detrended because of the non-linear growth curve. The counts of some elements also have long-term trends [ 12 , 13 ]. The best example is Ca, which decreases from the pith to the bark.…”
Section: Methodsmentioning
confidence: 99%
“…Lageard et al [ 4 ] demonstrated that Scots pine is a suitable species to study the scale and timing of past lead pollution in industrial areas of England. Gavrikov et al [ 12 , 13 ] studied the distribution trends of elements in stems of four widespread Siberian conifers. A few elements (Ca, P, and Co) had consistent trends in the stems irrespective of species.…”
Section: Introductionmentioning
confidence: 99%